Analysis of the effect of cutting mode and coolant on the formation of burrs when drilling aluminum alloy AK5Mch - O. P. Evdokimova; D. S. Makashin (Омский научный вестник)
Aluminum alloy Ak5m is widely used in the aerospace and automotive industries to replace heavier alloys. This is due to its excellent properties of high specific strength, high corrosion resistance, good formability and low manufacturing cost. Ductility and heat generation during drilling AK5MCH often leads to the formation of burrs at the inlet and outlet from the surface of the workpiece. This study shows the effect of cutting speed and drilling conditions on the formation of burrs in the AK5MCH alloy. Drilling is carried out using coolant and without coolant using drills made of high-speed steel with a diameter of 6,0 mm with cutting speeds of 20, 42 and 60 m/min at a constant feed of 0,15 mm/rev. This study showes that drilling AK5MCH with a cutting speed of 42 m/min using a coolant is advantageous, as it leads to the least tool wear and minimal burr formation.